Photoresponse of Nanocomopsite Titanium Dioxide with Transitional Metal Doping - , Shu-Wei Lin, Yong X. Gan (Archives of Current Research International, 2016)
Photoelectrochemical fuel cells consisting of pure TiO2 and doped TiO2 with transitional metals, Ni, Cu, Fe, or Co, were made to decompose environmentally hazardous material and to generate electricity by capturing solar irradiations. The titanium dioxide porous structure was developed through electrochemical oxidation of pure Ti sheet in the solution with ethylene glycol, and ammonium fluoride. Four different solutions containing nickel (II) chloride, copper sulfate, iron (III) nitrate, and cobalt (II) acetate tetrahydrate were used to dope the TiO2 nanostructure. The morphology of the nanostructure was analyzed by scanning electron microscopy. The environmentally hazardous material, car coolant, was studied for the photochemical reaction. It is found that all of the specimens are able to generate potential differences between two electrodes with different magnitudes. Co doped TiO2 nanostructure is the only sample that can harvest the visible light energy. It is concluded that TiO2 and the doped materials have the ability to generate electricity and to decompose environmentally hazardous materials.